2021
DOI: 10.1021/jacs.1c02068
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Carbodiimide Guanylation by a Nucleophilic, High Spin Iron(II) Imido Complex

Abstract: Reduction of the three-coordinate iron(III) imido [Ph 2 B( t BuIm) 2 FeNDipp] (1) affords [Ph 2 B( t BuIm) 2 Fe NDipp][K(18-C-6)THF 2 ] (2), a rare example of a high-spin (S = 2) iron(II) imido complex. Unusually for a late metal imido complex, the imido ligand in 2 has nucleophilic character, as demonstrated by the reaction with DippNH 2 , which establishes an equilibrium with the bis(anilido) complex [Ph 2 B( t BuIm) 2 Fe(NHDipp) 2 ][K(18-C-6)THF 2 ] (3). In an unusual transformation, formal insertion of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 57 publications
(99 reference statements)
4
30
0
Order By: Relevance
“…1, right), 8,27,28 but also to that of the anionic iron(II) imide [(Ph 2 B{ t BuIM} 2 )Fe(NDipp)] À (d ¼ 0.46 mm s À1 , jDE Q j ¼ 1.45 mm s À1 , at 80 K). 20 The IS of K{m} [1] ranges between those of the diferric and diferrous silylamide complexes [(L 2 Fe) 2 (m-S)] 2À,0 at 80 K with unambiguous trigonal iron(II) (d ¼ 0.59 mm s À1 ) and iron(III) ions (d ¼ 0.29 mm s À1 ). 29 The large QS of K{m}[1] is remarkable and would generally point to divalent iron.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, right), 8,27,28 but also to that of the anionic iron(II) imide [(Ph 2 B{ t BuIM} 2 )Fe(NDipp)] À (d ¼ 0.46 mm s À1 , jDE Q j ¼ 1.45 mm s À1 , at 80 K). 20 The IS of K{m} [1] ranges between those of the diferric and diferrous silylamide complexes [(L 2 Fe) 2 (m-S)] 2À,0 at 80 K with unambiguous trigonal iron(II) (d ¼ 0.59 mm s À1 ) and iron(III) ions (d ¼ 0.29 mm s À1 ). 29 The large QS of K{m}[1] is remarkable and would generally point to divalent iron.…”
Section: Resultsmentioning
confidence: 99%
“…For low-spin complexes, mostly found for isolable and rather unreactive late 3d-metal imidos, few reports of one-electron oxidation showed contraction of the imido metal bond. 12,16–20 This can be explained by a metal centred oxidation, accompanied with ion radius contraction as well as increased p → d donation and depopulation of anti -bonding molecular orbitals. 5,21 Contrastingly, in the only two reports of oxidation of high-valent high-spin 3d-metal imidos M–N bond elongation took place (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…61 Crucially, the isomer shi was similar to those obtained for the four-coordinate Fe(III) imidyl complexes reported by Betley of 0.28 mm s À1 for ( Ar L) FeCl(NC 6 H 4 -p-t Bu) and 0.26 mm s À1 for ( Ar L)FeCl(NAd), 30 and the three-coordinate Fe(III) imido complex reported by Smith of 0.25 mm s À1 for Ph 2 B( t BuIm) 2 Fe]NDipp (Ph 2 B( t BuIm) 2 ¼ bis(3-tert-butylimidazol-2-ylidene-1-yl)(diphenyl)borate). 32 In addition, it is smaller than those of the three-coordinate Fe(III) imido complexes reported by Betley of 0.44 mm s À1 for ( Ar L)Fe] N(C 6 H 4 -p-t Bu), 0.47 mm s À1 for ( Ar L)Fe]NMes, and 0.37 mm s À1 for ( Ar L)Fe]NAd and by Holland of 0.47 mm s À1 for ( Me,Dipp Nacnac)Fe]NAd ( Me,Dipp Nacnac ¼ N,N 0 -bis(2,6-di-isopropylphenyl)penta-2,4-diiminato). 26,30,62 Notably, the isomer shi is greater than the structurally characterized Fe(IV) monoand bis-imido complexes (Tables S6 and S7 †).…”
Section: Resultsmentioning
confidence: 99%
“…4,5 In addition, high-spin states are rare among these compounds, with most of them being in low- and intermediate-spin states. 3,6–35 Many of the terminal imido complexes of Fe characterized to date contain traditional closed-shell imido ligands, represented as NR 2− (R = alkyl, aryl). 3 It has been shown that inducing a weak ligand field around the metal center enables the isolation of the open-shell imidyl ligand with a radical on its N, represented as ˙NR − .…”
Section: Introductionmentioning
confidence: 99%
“…Our group is interested in iron imide complexes for their potential as catalytic species in iron-catalyzed C−N bond formation. Several examples of isolable, mononuclear iron imides 20 (1, eq 1) 24 and mesityl azide (MesN The stability of complex 2 allowed us to determine its molecular structure by X-ray crystallography (Figure 1). Similar to the structures of related N-adamantyl (βdiketiminato)iron imides, 22,23 2 contains a three-coordinate iron center that is planar, with bond angles that sum to 360.0(2)°.…”
mentioning
confidence: 99%